2013
DOI: 10.1016/j.jml.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

“If a lion could speak …”: Online sensitivity to propositional truth-value of unrealistic counterfactual sentences

Abstract: People can establish whether a sentence is hypothetically true even if what it describes can never be literally true given the laws of the natural world. Two event-related potential (ERP) experiments examined electrophysiological responses to sentences about unrealistic counterfactual worlds that require people to construct novel conceptual combinations and infer their consequences as the sentence unfolds in time (e.g., “If dogs had gills…”). Experiment 1 established that without this premise, described conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 88 publications
9
52
3
1
Order By: Relevance
“…These results provide further evidence that readers have set up a mental representation of the described counterfactual world, and can interpret events according to this plausible counterfactual world in the earliest moments of processing (e.g. Ferguson et al, 2010;Nieuwland, 2013;Nieuwland & Martin, 2012). Moreover, the fact that this pattern of inconsistency detection did not differ between the counterfactual-counterfactual and factual context conditions suggests that similar pragmatic constraints were activated by this counterfactual world as within a factual context.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…These results provide further evidence that readers have set up a mental representation of the described counterfactual world, and can interpret events according to this plausible counterfactual world in the earliest moments of processing (e.g. Ferguson et al, 2010;Nieuwland, 2013;Nieuwland & Martin, 2012). Moreover, the fact that this pattern of inconsistency detection did not differ between the counterfactual-counterfactual and factual context conditions suggests that similar pragmatic constraints were activated by this counterfactual world as within a factual context.…”
Section: Discussionsupporting
confidence: 52%
“…Similar results have been found using unrealistic counterfactual sentences (e.g. "If dogs had gills, Dobermans would breathe underwater"), indicating that the ability to make counterfactual inferences does not rely on preexisting knowledge about reality (Nieuwland, 2013). Nieuwland (2012) has also presented evidence that different neural circuits might underlie these truth-value judgements for real-world and counterfactual-world utterances.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Whereas sentence truth value N400 effects have often been observed for straightforward affirmative sentences (e.g., Nieuwland, 2013;Nieuwland & Martin, 2012;Hagoort et al, 2004;Kounios & Holcomb, 1992;Fischler et al, 1983), a substantial body of literature suggest that these effects do not always occur in sentences that contain negation operators or negative quantifiers such as "no" or "few" (e.g., Nieuwland, in press; Urbach Nieuwland & Kuperberg, 2008;Kounios & Holcomb, 1992;Fischler et al, 1983). In negative sentences like "A robin is not a tree," N400 amplitude is not reduced for true sentences compared to false sentences, and some older studies have reported N400 amplitude is not sensitive to negation at all (e.g., Kounios & Holcomb, 1992;Fischler et al, 1983).…”
Section: Sentence Truth Value N400 Effectsmentioning
confidence: 99%